Sidescan sonar imagery of widespread fossil and active cold seeps along the central Chilean continental margin - Klaucke, Ingo; Weinrebe, Wilhelm; Linke, Peter; Kläschen, Dirk; Bialas, Jörg (Geo-marine letters, 2012)
The central Chilean subduction zone between 35°S and 37°S was investigated in order to identify, document and possibly understand fluid flow and fluid venting within the forearc region. Several areas were mapped using multibeam bathymetry and backscatter, high-resolution sidescan sonar, chirp subbottom profiling and reflection seismic data. On a subsequent cruise ground-truthing observations were made using a video sled. In general, this dataset shows surprisingly little evidence of fluid venting along the mid-slope region, in contrast to other subduction zones such as Central America and New Zealand. There were abundant indications of active and predominantly fossil fluid venting along the upper slope between 36.5°S and 36.8°S at the seaward margin of an intraslope basin. Here, backscatter anomalies suggest widespread authigenic carbonate deposits, likely the result of methane-rich fluid expulsion. There is unpublished evidence that these fluids are of biogenic origin and generated within the slope sediments, similar to other accretionary margins but in contrast to the erosional margin off Central America, where fluids have geochemical signals indicating an origin from the subducting plate.